2022
DOI: 10.3389/fnins.2022.952288
|View full text |Cite
|
Sign up to set email alerts
|

EMG feedback outperforms force feedback in the presence of prosthesis control disturbance

Abstract: Closing the prosthesis control loop by providing artificial somatosensory feedback can improve utility and user experience. Additionally, closed-loop control should be more robust with respect to disturbance, but this might depend on the type of feedback provided. Thus, the present study investigates and compares the performance of EMG and force feedback in the presence of control disturbances. Twenty able-bodied subjects and one transradial amputee performed delicate and power grasps with a prosthesis in a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…These tasks require coordination of elbow angle and wrist EMG to complete the reach. This paradigm differed from other similar studies into proprioceptive feedback by using a ballistic reach paradigm, which prevented subjects from incorporating feedback into their task performance and allowed us to investigate solely the impact of feedback on improvements to feedforward control [ 10 , 13 , 41 , 42 ]. Our results provide some insight into how artificial joint speed feedback may be used to improve control of a myoelectric prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tasks require coordination of elbow angle and wrist EMG to complete the reach. This paradigm differed from other similar studies into proprioceptive feedback by using a ballistic reach paradigm, which prevented subjects from incorporating feedback into their task performance and allowed us to investigate solely the impact of feedback on improvements to feedforward control [ 10 , 13 , 41 , 42 ]. Our results provide some insight into how artificial joint speed feedback may be used to improve control of a myoelectric prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, artificial sensory feedback has received much attention over the past decade [ 3 , 4 ]. Typically, this takes the form of sensory substitution feedback, where the information provided from missing sensory organs is communicated to the user via an alternative method such as vibrotactile [ 5 10 ] or auditory stimuli [ 11 13 ], or via direct nerve stimulation [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proportional myoelectric control was robust and reliable despite the tight fit on the forearm and the fact that the subjects moved the prosthesis to reach and grasp the target object. Now, when the technical platform has been developed and assessed, and the anatomically congruent encoding (coupled scheme) verified as effective, we can proceed and evaluate the impact of closedloop control on the sensorimotor integration aspects during prolonged and/or more challenging prosthesis use (e.g., introducing disturbance [43], intermittent feedback). Indeed, we assume that the true benefits of anatomically congruent feedback would be expressed in these paradigms, when the subjects have enough time to integrate the feedback into the internal representation of the motors task and develop internal models of prosthesis behavior [14].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on an EMG feedback-based interface that has previously been shown to outperform other non-invasive feedback approaches to prosthesis force control [25,32]. We elicited a wide range of success rates by enforcing task execution at different speeds using a time-band methodology, similar to previous studies that investigated motor control of natural movements [16,22].…”
Section: Learning Induced Changes In the Saf For An Emg Feedback-base...mentioning
confidence: 99%